2020
DOI: 10.1021/acsanm.0c01445
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Optical Nonlinearities of Nanometer-Thick Sb2Te3 Thin Films: Implications for Mode-Locking and Super-resolved Direct Laser Writing

Abstract: 2D materials are currently very promising candidates for various photonic applications. Optimizing their optical nonlinearities requires a thorough adjustment of several properties including the film thickness. In this work thin Sb2Te3 layers with different thicknesses (ranging from 2.5 to 50 nm) are prepared by the electron beam deposition technique, and then they are properly annealed in order to achieve significant third order nonlinearities. The film structure and morphology are extensively studied by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
(154 reference statements)
0
17
0
Order By: Relevance
“…And the figure of merit (FOM) for the third-order optical nonlinearity (FOM Im |Imχ (3) /α 0 |) (Dong et al, 2016) can be determined to be −2.7 × 10 -13 (esu cm) and 8.9 × 10 -13 (esu cm) for 532 and 650 nm, respectively. The FOM of β-GaS film is higher than the reported values of WS 2 and Sb 2 Te 3 thin films (Dong et al, 2016;Verrone et al, 2020), indicating the β-GaS is a promising candidate for applications in optical limiting and ultrafast saturable absorber.…”
Section: Open Aperture Z-scanmentioning
confidence: 67%
See 1 more Smart Citation
“…And the figure of merit (FOM) for the third-order optical nonlinearity (FOM Im |Imχ (3) /α 0 |) (Dong et al, 2016) can be determined to be −2.7 × 10 -13 (esu cm) and 8.9 × 10 -13 (esu cm) for 532 and 650 nm, respectively. The FOM of β-GaS film is higher than the reported values of WS 2 and Sb 2 Te 3 thin films (Dong et al, 2016;Verrone et al, 2020), indicating the β-GaS is a promising candidate for applications in optical limiting and ultrafast saturable absorber.…”
Section: Open Aperture Z-scanmentioning
confidence: 67%
“…The Z-scan curves were fitted using the standard Z-scan theory (Sheik-Bahae et al, 1990), and the effective nonlinear absorption coefficients were determined to be −1.8 × 10 -8 m/W and 4.9 × 10 -8 m/W for 532 and 650 nm, respectively. Pervious results demonstrate that the film thickness has a significant influence on the NLO response of 2D material (Zhang et al, 2018;Verrone et al, 2020). However, the experimental data of β-GaS thin film with different thickness was not available due to the limitation of film deposition system and the low laser damage threshold of few-layer thin film.…”
Section: Open Aperture Z-scanmentioning
confidence: 99%
“…Our group had previously demonstrated that Sb 2 Te 3 films thicker than 6 nm exhibit significant nonlinear absorption, while nonlinear refraction is negligible [7]. For this reason, in the case of the 10 nm thick Sb 2 Te 3 films studied in this work, the open aperture recordings were of main interest.…”
Section: Nonlinear Optical Studiesmentioning
confidence: 86%
“…A quartz microbalance was used to measure the Sb 2 Te 3 thickness with a precision of ±0.2 nm. A thickness of 10 nm was chosen because we had previously demonstrated that the maximum nonlinearity for the Sb 2 Te 3 material by our deposition method was between 8 and 11 nm [7]. The layers were capped by a 2 nm thick SiO 2 layer.…”
Section: Thin Film Depositionmentioning
confidence: 99%
See 1 more Smart Citation